Teacher-student interactions and laboratory learning environments in biology classes in Thailand - Kijkosol, Duangsmorn (Curtin University, 2005)
The first purpose of the study described in this thesis was to provide validation information of three questionnaires that were modified and translated into the Thai language, namely, the Questionnaire on Teacher Interaction (QTI), the Science Laboratory Environment Inventory (SLEI), and the Attitude to Biology Class (ABC). A second purpose was to determine students' perceptions of teacher-student interactions and laboratory learning environments and their attitudes to biology classes in secondary schools in Thailand. A sample of 1,194 students from 37 biology classes in 37 schools completed the three questionnaires. The results of the study showed that most students in secondary schools of Thailand have moderately positive attitudes to their biology class. Students perceived their teachers as having good leadership, being helping/friendly, and understanding, but seldom uncertain, dissatisfied or admonishing. They also perceived that sometimes their teachers were strict, however allowing students responsibility and freedom. In biology laboratories, they perceived the environments as employing good student cohesiveness, less open-endedness and integration of the theory and practical, the rules were not clear and the materials were not good and insufficient. There were differences between students' actual and ideal perceptions of classroom interactions and laboratory learning environments. Students preferred teachers who showed strong leadership, were more helping and understanding, who gave their students more responsibility and freedom, and who were less uncertain, dissatisfied, admonishing and strict.Also, students preferred a biology laboratory environment with higher levels on the scales of Open-Endedness, Integration, Rule Clarity, and Material Environment but not Student Cohesiveness. Some commonality between the QTI and the SLEI scales was found in their contributions to the variance in student attitudes to biology classes. So now the QTI and the SLEI can be used by biology teachers and other science teachers in secondary schools who wish to improve science teaching and learning in Thailand.